Aptamer-conjugated gold nanoparticles and their diagnostic and therapeutic roles in cancer - Deng, Guozhen; Zha, He; Luo, Hongzhi; Zhou, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
The incidence rate and mortality of cancer are rapidly increasing. Effective detection and therapeutic interventions for cancer will help reduce the burden of cancer pain. The sensitivity and specificity of existing cancer diagnosis methods are poor. Surgical treatment is not feasible in advanced stages of cancer, while radiotherapy and chemotherapy often have side effects. Aptamers can selectively and exclusively bind to biomarkers and have therefore gained attention as ligands to be targeted for cancer detection and treatment. Gold nanoparticles (AuNPs) are important carriers that help molecules penetrate cells. Because of their light scattering characteristics, good biocompatibility, and ease of surface modification with targeted agents, AuNPs are considered promising nanocarriers for cancer diagnosis and treatment. The aptamer AuNP targeting delivery system has the advantages of good targeting, high sensitivity, low immunogenicity, and low side effects. Aptamer AuNPs have built a bridge for cancer markers to be used for early and efficient diagnosis and precise treatment. In this review, we summarize the latest progress in the application of aptamer-modified AuNPs in cancer targeted diagnosis and delivery of therapeutic agents to cancer cells and emphasize the prospects and challenges of transforming these studies into clinical applications.